The Perception of Cross Sectoral Early Years Educators on their Role in Developing the Voice and Agency of 3-7 Year Olds with Specific Regard to Minority Children - McClafferty, Daríona (Marino Institute of Education, 2020)
Regulatory bodies such as the Department of Education and Skills (2011) and the National Curriculum for Curriculum and Assessment (2016) outline the need for connections and consistency across philosophies in early years educational sectors for 3-7 year olds. However, in many cases the connections across philosophies are nonexistent in reality. The philosophies of both preschool and primary education encompass a broad range of areas. This study focuses specifically on what is occurring in terms of the voice and agency of minority children. This qualitative study was designed under an interpretivist paradigm. Focus groups and interviews were the tools chosen for data collection. The data was collected and analysed from 10 early years educator participants, 5 preschool and 5 primary educators to investigate the perception of their role regarding voice and agency of minority children. The study found that there are distinct differences in policies implemented in the early years and primary education sectors in regards to the voice and agency of minority children. There were also differences between the single and multi-denominational settings in terms of policies of inclusion that have implications on the voice and agency of minority children. There were also indications that these teachers do perceive themselves as having a role in developing the voice and agency of minority children. However, they felt that this role is most effective when the intersecting structures in a child’s life all work together. With reference to pertinent literature, recommendations for best practice are made.
Keywords: early year policies; voice and agency; minority children; qualitative; interpretivist